2020
DOI: 10.20944/preprints202012.0038.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sociodemographic Predictors of Changes in Physical Activity, Screen Time, and Sleep Among Toddlers and Pre-Schoolers in Chile During the COVID-19 Pandemic

Abstract: The aim was to examine the sociodemographic predictors associated with changes in movement behaviours (physical activity, screen time and sleep) among toddlers and pre-schoolers during the early stages of the coronavirus disease 2019 pandemic in Chile. Caregivers of 1- to 5-year-old children completed an online survey between March 30th and April 27th, 2020. Information about the child's movement behaviours before (retrospectively) and during the pandemic, as well as family characteristics were reported. In to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Third, subjects at such age are dependent on parents’ decisions regarding their lifestyle. Finally, the geographic/urban environment could influence physical activity and sleep patterns during the early years [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, subjects at such age are dependent on parents’ decisions regarding their lifestyle. Finally, the geographic/urban environment could influence physical activity and sleep patterns during the early years [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status was measured according to the level of average income per family unit. Socioeconomic factors seem to be lifestyle determinants during the COVID-19 lockdown in children and adolescents [ 20 ]. Finally, the students were weighed and measured in light clothing and barefoot.…”
Section: Methodsmentioning
confidence: 99%
“…Living in rural areas was frequently associated with fewer emotional changes in children. During the COVID-19 pandemic, living in rural areas was also reported as a factor positively related to smaller decreases in physical activity, declines in sleep quality and increases in screen time (25). In this line, a study conducted in 14 countries showed that preschoolers that were able to go outside during the pandemic were more likely to meet the PA guidelines (49).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that more factors may contribute to the emotional and behavioral changes during the pandemic. However, strategies to mitigate the negative socioemotional issues derived from the pandemic should include multilevel approaches for promoting more physical activity, less screen time and more and better sleep quality (25, 58). Policies must consider toddlers and preschoolers in their design and impact assessment due to a year in pandemic in the life of them is expected to have more considerable impact on their future development than in adults (43, 58, 59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation